Just In Time! Assessment of Internal Medicine Resident Point of Care Ultrasound (POCUS) Attitudes and Behaviors After Spaced Intervention at Two Residency Programs - Kevin Piro; Patricia Carney; Christopher Smith (CINQUILL Medical Publishers Inc., 2024)
Point of care ultrasound (POCUS) is a complex psychomotor skill that requires scaffolded support for skill acquisition. However, the effect of spaced curricular elements on learner POCUS behaviors are not clearly understood. Using a multi-site observational cross-sectional survey study, we measured resident baseline POCUS use, behaviors, and attitudes and then implemented POCUS workflow and just-in-time POCUS curricula during internal medicine resident ward rotations and assessed changes. Self-reported personal and team POCUS use and documentation habits all improved between baseline and the just-in-time teaching. Personal POCUS use correlated with team POCUS use (ρ=0.431; p<0.001) and co-resident POCUS use (ρ=0.242; p=0.035). Attending POCUS use correlated with team POCUS use (ρ=0.523; p< 0.001), but not personal use. Overall, we found moderate, but statistically significant, improvements in reported resident and team performance of POCUS and documentation habits, suggesting that just-in-time interventions may promote POCUS use. Co-learning also appears to be a key influencer for POCUS use.